Extent of Adoption and Constraints in Boro Rice Cultivation Faced by theFarmers in Darbhanga District of Bihar - Prasad, Satya Narayan; Choudhary, A.K. (Indian Journal of Extension Education, 2010)
This study was carried out in the Biraul, Kusheshwarsthan and Ghanshyampur blocks of Darbhanga district of Bihar. The productivity of boro rice is heavily dependence upon the adoption of different components of technology in the field condition. Therefore, it will be of strategic relevance to periodically assess the adoption behaviour of boro rice in Biraul, Kusheshwarsthan and Ghanshyampur block of Darbhanga district which have immense potentiality for boosting the rice production. The study revealed that the extent of adoption of different components of boro rice technology were highest in the area of land preparation (70.00%) followed by transplanting of seedling (46.66%) and lowest in plant protection measures (11.66%). Out of seven selected variables undertaken in the study, six variables were found to be highly correlated with extent of adoption. But multiple regression analysis indicated that the variables education was the main potential predictor of extent of adoption. The variables education and annual income had independence and direct influence on the extent of adoption of boro rice production technology. The variable age of farmers had negatively and significantly contributed with extent of adoption of boro rice production technology. It means that young farmers were good adopter of new farm technology than aged one. Major constraints associated with non adoption of boro rice production technology were lack of regular and effective training (87.50%) followed by high cost of cultivation (83.33%) and non-availability of credits (81.66%).